KETERLIBATAN AKTOR DALAM PENGEMBANGAN EKOWISATA DI TAMAN WISATA PERAIRAN GILI TRAWANGAN LOMBOK - Murdana, I Made (Institut Agama Hindu Negeri Gde Puda Mataram, 2022)
Ecotourism as a development concept has been believed to be able to ensure the sustainability of the destination. In addition, the dynamics of development between destinations experience are different situations. The difference lies in the influencing factor. In ensuring the sustainability of ecotourism development, one of which requires collaboration of roles, commitments and contributions of actors in the development of ecotourism. The study of actors who influence development is a mandatory thing in determining policy directions. This study aims to determine the stratification of actors in the development of ecotourism in the Gili Trawangan. This study uses a qualitative approach by utilizing the ISM system analysis tool. The expert respondents used were 11 people. The research resulting, the actors involved in the growth of ecotourism were categorized as a result of this study. Results are in the DP-D matrix quadrant in 3 cells. The sub-elements of the Ministry of Tourism and KKP, Local Government, and Universities are located in the quadrant IV (independent), with the largest driving force. Sub-elements of local institutions and tourism associations are concentrated in Quadrant III (Linkage). Sub-elements of commercial or industrial organizations, as well as certifying bodies, occupy Quadrant II (dependent). The study's findings support the notion that the Ministry of Tourism, KKP, Local Government, and Universities are the primary actors that must act first in order to set off additional sub-elements. The study's findings aid in the formation of future growth plans as well as the emphasize of the tourism penta helix's capacities.